Symmetric structures - Isabelle Haïk (Corela)
The present article bears on the NPN construction (face to face and student after student), investigated in an illuminating way in Jackendoff (2008). It proposes an account of NPN forms in which they are lexical items. Contrary to what is commonly assumed, there are two types of NPNs, depending on whether the head of the construction is P (face to face), forming a lexical small clause, or N (student after student), forming a coordinate N. One important theoretical point raised by such constructs is that they are ternary structures and thus seem to contradict Kayne’s (1984) universal condition on binary branching. I will claim that, if Kayne’s principle is cognitive, in that it reflects the working of mental computation, then these ternary constructions, which should be impossible, are indeed possible, but only because there is one specific way for the brain to allow for their formation. Lastly, the article considers a number of properties of NPNs and accounts for them.